International trade and environmental disputes : an analysis of Article XX of the General Agreement on Tariffs and Trade (1994) and environmental policies of the developing and developed world - Manjoro, Faith Tendayi (Rhodes University, Faculty of Law, Law, 2007)
A major problem emanating from the trade/environment conflict is the use of trade measures, such as restrictions and sanctions, as tools for environmental protection. Proponents of free trade argue that the use of these measures is tantamount to abuse of environmental standards for protectionist ends. This is particularly so if the imposition of the standard amounts to a unilateral act which blocks the entry of a specified product into the market of another member state for reasons other than environmental protection. Environmentalists at the same time argue that free trade will lead to environmental degradation and therefore advocate for the use of trade-restrictive measures to safeguard against the destruction of the environment. The GATT has proved problematic when it comes to the resolution of trade/environment conflicts. The GATT aims at trade liberalisation yet most environmental policies are enforced through trade-restrictive devices like quotas and licences. Article XX of the GATT is anomalous: it does not explicitly mention the environment, yet member states rely on it as an environmental protection clause. This thesis discusses the various issues emanating from the trade/environmental debate. The history of Article XX is reviewed and the issues that arise in the adjudication of Articles XX (b) and (g) in a trade/environment context are analysed in light of the decisions by the GATTIWTO dispute settlement bodies. The role played by Multilateral Environmental Agreements (MEAs) in protecting the environment is discussed. However, the relationship between MEAs and the WTO is also scrutinised as these rule-making bodies often come into conflict: firstly, because they serve two differing interests - on the one hand, MEAs allow for the use of trade restrictive measures in environmental agreements and on the other, the WTO calls for unrestricted trade unless exceptional circumstances exist; and secondly, member states that are party to both the WTO and MEAs are often forced to subscribe to international trade rules that are incompatible with those in environmental agreements. The trade/environmental debate is important to both the developed and developing worlds. The developed world is in favour of environmental policies which protect the environment from degradation. On the other hand, the developing world is in desperate need of the benefits of trade liberalisation so as to cater for high unemployment rates and poor economic growth. The question thus arises as to whether, when environmental issues are promoted, developing countries will not suffer at the expense of developed nations which may engage in protectionist measures under the pretext of environmental conservation. The divide between developed and developing countries is illustrated in Chapter 5 through case studies on coal mining in the USA and South Africa. The conclusion reached is that total co-operation is essential between developed and developing states for success in safeguarding the environment from degradation. Accordingly, the trade/environmental debate cannot be isolated from the conflicting approaches in developed and developing countries. The conclusions in the final chapter seek to strike a balance between trade liberalisation and environmental protection. Recommendations are made on how the trade/environmental challenges could be dealt with and the regulation of trade restrictive devices to exclude, or at least limit, protectionism.
Keywords: World Trade Organization; General Agreement on Tariffs and Trade (Organization); Environmental protection; Environmental degradation; Free trade -- Environmental aspects; Foreign trade regulation; International trade